Thymic malignancies: Moving forward with new systemic treatments. (May 2016) - Remon, J.; Lindsay, C.R.; Bluthgen, M.V.; Besse, B.
Highlights: Thymic neoplasms are rare malignant tumours. Platinum-based chemotherapy remains the principal treatment in metastatic tumours. Cytotoxic therapies, targeted therapies and immunotherapy are promising second-line treatments. Abstract: Thymic neoplasms are rare malignant tumours, for which the mainstay of treatment is surgical resection. Platinum-based chemotherapy remains the principal treatment in metastatic tumours, with no standard second-line option. Many genes implicated in tumour onset, growth and metastases have been demonstrated to be therapeutic targets in thymic malignancies. Other current efforts to improve outcomes are based on a better understanding of the stromal compartment and tumour microenvironment, facilitating novel therapeutic approaches such as angiogenesis inhibition and immunotherapy. This review seeks to explore the present cutting edge for systemic treatment of advanced thymic neoplasms, examining novel agents under clinical investigation such as cytotoxic therapies, targeted therapies and immunotherapy. Based on the literature review we have selected potential treatment schemes, which could be used in daily clinical practice as second-line treatment.